HANS JONAS ON THE ETHICS OF TECHNOLOGY - Raja Oloan Tumanggor (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2020)
This paper highlights Hans Jonas' technological ethic. For Jonas, traditional ethics is no longer adequate because the dynamics of modern technology are increasingly sophisticated. Initially, technology only helped humans learn natural laws so that nature could be used by humans according to their needs. However, the more advanced the technology, the side effects are also out of control and cannot be controlled. Therefore, Jonas offers ethical responsibility in the context of technology. This study examines Jonas's view of how humans should behave in today's technological developments. The method used is a qualitative method by analyzing Jonas' primary writings on technology ethics, then trying to describe them descriptively and critically. First of all, a brief biography of Jonas will be presented. Then discussed step by step his thoughts on technological ethics that come from primary and secondary sources. The result is that according to Jonas, humans have to change their way of life (lifestyle) in producing, consuming and caring about the environment. By creating a sense of human responsibility can prevent future calamities. This awareness is called Jonas with the principle of future responsibility. Studi ini menyoroti etika teknologi oleh Hans Jonas. Bagi Jonas, etika tradisional tidak lagi memadai karena dinamika teknologi modern semakin canggih. Pada awalnya teknologi hanya membantu manusia mempelajari hukum-hukum alam sehingga alam dapat dimanfaatkan oleh manusia sesuai dengan kebutuhannya. Namun, semakin canggih teknologi tersebut, efek sampingnya menjadi tidak terkendali. Oleh karena itu, Jonas menawarkan sebuah tanggung jawab etis dalam konteks teknologi. Studi ini mengkaji pandangan Jonas tentang bagaimana seharusnya manusia berperilaku dalam perkembangan teknologi saat ini. Metode yang digunakan adalah metode kualitatif dengan menganalisis tulisan utama Jonas tentang etika teknologi, kemudian mencoba mendeskripsikannya secara mendalam dan kritis. Pertama-tama, terdapat biografi singkat Jonas. Kemudian pemikirannya tentang etika teknologi yang bersumber dari sumber primer dan sekunder dibahas selangkah demi selangkah. Hasilnya adalah, menurut Jonas, manusia harus mengubah cara hidup (gaya hidup) dalam memproduksi, mengonsumsi, dan peduli terhadap lingkungan. Dengan menciptakan rasa tanggung jawab manusia, musibah di masa depan dapat dicegah. Kesadaran ini disebut oleh Jonas sebagai prinsip tanggung jawab masa depan.